Safe-Sex Behavioral Intention of Chinese College Students: Examining the Effect of Sexual Knowledge Using the Theory of Planned Behavior - Wang, Xin; Jin, Yuanqing; Tian, Mengqin; Zhuo, Qinzi; Lin, Chien-Liang; Hu, Pengfei; Wang, Ting (Frontiers in Psychology, 2022)
Numerous contemporary studies have examined safe sexual behavior among college students. In China, families are reluctant to discuss sexual behavior, thus understanding and exploring the sexual knowledge of college students and the promotion of safe sexual behavior is essential. On the basis of the theory of planned behavior (TPB), a cognitive behavioral theory that is widely used to predict human social behavior, we conducted an in-depth investigation of the factors influencing the sexual behavioral intentions of Chinese college students. We referenced the relevant literature to develop a TPB-based model for analyzing differences in sexual knowledge. Our statistical analysis revealed the following: (1) subjective norms and behavior control are key variables that influence the safe sexual behavior of college students; (2) attitudes and safe-sex behavioral intentions are influential in groups with extensive sexual knowledge; (3) behavioral control and subjective norms influence the differences in the comparative sexual knowledge of students. On the basis of the present results, we propose research recommendations and directions for the development of sex education in China.